Implementation of Pricing Strategies to Increase Sales in The Digitalization Era - Faiqoh, Dina Nadiyah; Riyadi, Selamet; Lestari, Setyani Dwi; Mudjijah, Slamet (PT. Anagata Sembagi Education, 2024)
Pricing strategy plays an important role in marketing, influencing consumer decisions and sales volume. Methods such as penetration pricing, psychological pricing, and discount pricing are used to attract consumers' attention. Modern technologies, including data analytics and AI, enable rapid price adjustments to increase profitability and competitiveness. Pre-sales also collects important data to increase sales of new products. In the supply chain, traditional and direct channel pricing and service strategies are important for customer satisfaction. Dynamic pricing optimizes sales by adjusting prices based on consumer demand and perception. Consumer behavior analysis supports the effectiveness of pricing strategies, both cost-plus pricing for products and value-based pricing for services. In addition, price personalization strategies and money-back guarantees can increase customer trust and loyalty, especially in online markets, through real-time interactions and technology-based promotions.